2007
DOI: 10.1002/jbm.b.30862
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of human acellular tissue matrix by gamma irradiation: Histology, biomechanical property, stability, in vitro cell repopulation, and remodeling

Abstract: AlloDerm, a processed acellular human tissue matrix, is used in a number of surgical applications for tissue repair and regeneration. In the present work, AlloDerm serves as a model system for studying gamma radiation-induced changes in tissue structure and stability as well as the effect of such changes on the cell-matrix interactions, including cell repopulation and matrix remodeling. AlloDerm tissue matrix was treated with 2-30 kGy gamma irradiation at room temperature. Gamma irradiation reduced the swellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
11

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(60 citation statements)
references
References 51 publications
3
46
0
11
Order By: Relevance
“…This result further supports our findings of decreased biomechanical properties in hydrated tissue samples compared to dry samples. The substantial decrease in the thermal stability of the collagen matrices induced by hydration is consistent with previous studies [33][34][35]. In the present study, a significant difference in denaturation temperatures could be observed between MD and DM when compared to the MG matrix.…”
Section: Discussionsupporting
confidence: 95%
“…This result further supports our findings of decreased biomechanical properties in hydrated tissue samples compared to dry samples. The substantial decrease in the thermal stability of the collagen matrices induced by hydration is consistent with previous studies [33][34][35]. In the present study, a significant difference in denaturation temperatures could be observed between MD and DM when compared to the MG matrix.…”
Section: Discussionsupporting
confidence: 95%
“…Recently, it was shown that UBM-ECM had decreased uniaxial and biaxial mechanical properties after exposure to ethylene oxide (750 mg h À1 ), gamma irradiation (20 kGy) and electron beam irradiation (22 kGy) [82]. Several studies have also investigated the effects of a wide range of gamma irradiation exposure on dermis ECM [83,84]. At low dosages of gamma irradiation (<15 kGy), the strength and modulus of the scaffold increased, but the mechanical properties decreased above 15 kGy in a dose-dependent manner [83].…”
Section: Terminal Sterilizationmentioning
confidence: 98%
“…Several studies have also investigated the effects of a wide range of gamma irradiation exposure on dermis ECM [83,84]. At low dosages of gamma irradiation (<15 kGy), the strength and modulus of the scaffold increased, but the mechanical properties decreased above 15 kGy in a dose-dependent manner [83]. These changes appear to be due to an increase in collagen cross-linking due to the low dose of irradiation that levels off after approximately 5 kGy, along with collagen chain scission that continues to increase with the irradiation dose [84].…”
Section: Terminal Sterilizationmentioning
confidence: 99%
“…The amount of DNA fragments should be less than 200 bp, and nuclear materials should also stay undetected in 4', 6-diamidino-2-phenylindole (DAPI) or hematoxylin-eosin staining because DNA directly causes an immune response in the host body (1,106,107). DNA density can also be identified by using fluorometric stainings such as Hoechst (108)(109)(110).…”
Section: Evaluation Of Decellularization Processmentioning
confidence: 99%